Pemanfaatan Limbah Rumah Tangga (Sampah Anorganik) Sebagai Bentuk Implementasi dari Pendidikan Lingkungan Hidup - Novi Marliani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
This study aims to look at the form of the implementation of environmental education in the form of utilization of household waste (inorganic). nvironmental education is a process arbitrarily person to conduct environmental stewardship for sustainable survival. The increasing volume of waste requiring serious treatment of the waste management. Waste management does not use methods and techniques that are environmentally friendly waste management than would be a negative impact on health will also be very disruptive both residential environmental preservation, forest, rice fields, rivers and oceans. One of the forms of waste is household waste in the form of garbage anorgnik. This litter is very dangerous for health and the environment because it is made from inorganic sources of non-renewable natural and contains no chemicals, but its existence is only glimpsed one eye. Utilization of inorganic waste is one that can be done by the whole society to preserve the environment. This research is a descriptive study and a review of the literature. This study hopes to sustainable environmental education is expected to contribute knowledge to all levels of society on the importance of inorganic waste.